Sickle cell disease burden among tribal population of India: a narrative review - Nagisetty, Sahaja; Thatoju, Pavan K. (International Journal Of Community Medicine And Public Health, 2024)
Sickle cell disease (SCD) is a serious health challenge for tribal communities in India. These groups often have limited access to healthcare, lack proper awareness of the disease, and face higher rates of illness and death due to SCD. This review looks at the impact of SCD on tribal populations and identifies the states where the burden is most significant. A review of existing literature was conducted using sources like PubMed and Google Scholar. The focus was on studies that explored the prevalence of SCD among tribal populations. Various government reports and research articles were also examined to create a well-rounded understanding of how SCD affects these communities. The findings show that Madhya Pradesh and Chhattisgarh have particularly high rates of SCD compared to other parts of India. In these states, between 10% and 30% of tribal groups carry the sickle cell trait. Other states, such as Odisha and Maharashtra, have lower rates of the disease, suggesting that specific attention is needed in regions like Madhya Pradesh and Chhattisgarh to manage the disease more effectively. SCD continues to pose a serious public health issue in India’s tribal regions, particularly in certain states. It is essential to develop strategies that focus on raising awareness, improving access to healthcare, and managing SCD effectively in these communities. Public health efforts must include community involvement, education programs, and policy changes to better address the unique challenges faced by these populations.